2020
DOI: 10.3390/cells9102152
|View full text |Cite
|
Sign up to set email alerts
|

ARID2 Chromatin Remodeler in Hepatocellular Carcinoma

Abstract: Chromatin remodelers are found highly mutated in cancer including hepatocellular carcinoma. These mutations frequently occur in ARID (AT-rich Interactive Domain) genes, encoding subunits of the ATP-dependent SWI/SNF remodelers. The increasingly prevalent complexity that surrounds the functions and specificities of the highly modular BAF (BG1/BRM-associated factors) and PBAF (polybromo-associated BAF) complexes, including ARID1A/B or ARID2, is baffling. The involvement of the SWI/SNF complexes in diverse tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 79 publications
0
9
0
Order By: Relevance
“…Bioinformatics analysis of public databases and expression analysis of LIHC tissue samples showed that ARID4B was highly expressed in LIHC compared with adjacent normal tissues and strongly correlated with clinical features ( 35 ). The expression of ARID1A and ARID2 inhibited the proliferation and migration of LIHC cells and, thus, act as tumour suppressors ( 36 , 37 ). Therefore, the predicted roles of the ARID gene family members as a tumour suppressor or promoter in LIHC were in accord with our results, but validation from further experiments is required for an in-depth exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatics analysis of public databases and expression analysis of LIHC tissue samples showed that ARID4B was highly expressed in LIHC compared with adjacent normal tissues and strongly correlated with clinical features ( 35 ). The expression of ARID1A and ARID2 inhibited the proliferation and migration of LIHC cells and, thus, act as tumour suppressors ( 36 , 37 ). Therefore, the predicted roles of the ARID gene family members as a tumour suppressor or promoter in LIHC were in accord with our results, but validation from further experiments is required for an in-depth exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations of the ARID2 gene, which is involved in chromatin remodeling gene, are found in many human cancers. 51 , 52 In HCC, ARID2 mutations are reported to occur more frequently in HCV‐induced HCCs (6/43) in comparison to HBV‐related (1/50) and non‐viral‐related (2/44) HCC. 53 In our results, ARID2 mutations were observed in HCV‐positive tumors (6/34) and in HCV‐SVR tumors (1/35).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in ARID2 were significantly less frequent in HCV‐SVR tumors than in HCV‐positive tumors. Mutations of the ARID2 gene, which is involved in chromatin remodeling gene, are found in many human cancers 51,52 . In HCC, ARID2 mutations are reported to occur more frequently in HCV‐induced HCCs (6/43) in comparison to HBV‐related (1/50) and non‐viral‐related (2/44) HCC 53 .…”
Section: Discussionmentioning
confidence: 99%
“…[Tong et al [ 247 ] reviewed the biological mechanisms (especially DNA damage repair) mediated by SMARCAD1.] ARID2 (AT-rich Interactive Domain 2) genes also encode subunits of SWI/SNF remodellers, which is associated with hepatocellular carcinoma (see review by Loesch et al [ 248 ]).…”
Section: Key Structural Elements Mediating 3d Chromatin Interactionsmentioning
confidence: 99%